Application of Ag-based materials in high-performance lithium metal anode: A review. (10th January 2023) - Liu, Zhongxiu; Ha, Sihu; Liu, Yong; Wang, Fei; Tao, Feng; Xu, Binrui; Yu, Renhong; Wang, Guangxin; Ren, Fengzhang; Li, Hongxia
Highlights: The application of Ag-based materials in lithium metal anodes is summarized. The theoretical and mechanism of Ag-based lithium anodes are emphasized. Challenges and future prospects of application of Ag-based materials in lithium metal batteries are proposed. Abstract: Li metal is a promising candidate for battery anodes due to its high theoretical specific capacity (3860 mAh g −1 ) and low electrochemical potential (−3.04 V). Nevertheless, the challenges for Li metal include uncontrolled dendrites growth, unstable solid electrolyte interface, and infinite volume expansion during Li plating and stripping, which limit the further development of lithium metal anodes (LMAs). Introducing Ag-based materials in LMAs is regarded as one of the most effective solutions to solve the above-mentioned problems, which have received considerable attention because of their superior characteristics, such as high electrical conductivity, outstanding lithiophilicity, and excellent mechanical stability. Herein, we review the recent progress on the application of Ag-based materials in LMAs. Furthermore, the theoretical mechanism of Ag-based materials and their advantages in LMAs are emphasized. In addition, the relationship between their fabrication strategies, micro/nanostructures, and electrochemical performances is systematically discussed. Finally, the challenges and opportunities for the future research and application of Ag-based materials in lithium metal batteries are proposed based on the available academic knowledge.